Histone deacetylase 9 exacerbates podocyte injury in hyperhomocysteinemia through epigenetic repression of Klotho - Min Liu; Yang Zhang; Ping Zhan; Wenjuan Sun; Chuanqiao Dong; Xiaohan Liu; Yujie Yang; Xiaojie Wang; Yusheng Xie; Chengjiang Gao; Huili Hu; Benkang Shi; et al. (Elsevier, 2023)
Although hyperhomocysteinemia (hHcys) has been recognized as an important independent risk factor in the progression of end-stage renal disease and the development of cardiovascular complications related to end-stage renal disease, the mechanisms triggering pathogenic actions of hHcys are not fully understood. The present study was mainly designed to investigate the role of HDACs in renal injury induced by hHcys. Firstly, we identified the expression patterns of HDACs and found that, among zinc-dependent HDACs, HDAC9 was preferentially upregulated in the kidney from mice with hHcys. Deficiency or pharmacological inhibition of HDAC9 ameliorated renal injury in mice with hHcys. Moreover, podocyte-specific deletion of HDAC9 significantly attenuated podocyte injury and proteinuria. In vitro, gene silencing of HDAC9 attenuated podocyte injury by inhibiting apoptosis, reducing oxidative stress and maintaining the expressions of podocyte slit diaphragm proteins. Mechanically, we proved for the first time that HDAC9 reduced the acetylation level of H3K9 in the promoter of Klotho, then inhibited gene transcription of Klotho, finally aggravating podocyte injury in hHcys. In conclusion, our results indicated that targeting of HDAC9 might be an attractive therapeutic strategy for the treatment of renal injury induced by hHcys.